Association between Fetal Gender and the Labor Curve at Term Pregnancy - Gurung, Rubina Tamrakar; Sharma, P (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: Animal and pathologic models have provided evidence for a fetal influence on the labor process; however, the potential impact of fetal gender on the labor curve has gone largely unstudied. Objectives: To determine the association between fetal gender and first stage labor curve at term. Methods: This was a retrospective study. There were 330 patients enrolled in this study, who gave birth from January 2011 to December 2012 by reviewing the charts. A total of 500 charts were reviewed. Results: There were three hundred thirty (330) patients, out of which a total of 179 (54.2%) patients gave birth to males and 151 (45.8%) gave birth to females. Women who had a male fetus had a longer first stage of labor than women who carried a female fetus. The difference in the birth weight of the infants is statistically significant, male newborns were heavier at birth than female newborns. Conclusions: Term labor in the first stage was found to be slower in women who carried a male fetus compared with those with female fetus which is not statistically significant. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, page: 1-4